Natural monopolies in digital platform markets / Francesco Ducci. - Ducci, Francesco, 1987- (Global competition law and economics policy., 2020)
Competition policy debates on digital platform markets are often premised on the idea that market fragmentation and the standard forces of competition and entry may provide a potential solution to excessive concentration and market power. In this work, Francesco Ducci provides readers with a different perspective based on the theoretical lens of natural monopoly. Ducci explores this framework through the development of three case studies on horizontal search, e-commerce marketplaces, and ride-hailing platforms, investigating the strength and limit of potential (and often heterogeneous) sources of natural monopoly at play in each industry. Building on these case studies, the book then derives from the application of the natural monopoly framework general policy implications for digital industries by identifying the respective institutional flaws and shortcomings of ex ante and ex post approaches to market power as one of the central challenges in digital platform markets.